Disfungsi Perusahaan Daerah Air Minum Kota Surakarta dalam Penyediaan Air Bersih - Abidana Mazida; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The existence of clean water is very important because clean water is a basic need for human life and the environment. The availability of abundant clean water is certainly an indicator of welfare, public health, and environmental sustainability. The Surakarta City Regional Drinking Water Company as a provider of clean water services to the community is carried out in accordance with applicable regulations in order to realize clean water services that are decent, equitable, and sustainable. This study aims to determine the role of the Surakarta City Regional Drinking Water Company in implementing the provision of clean water to meet the needs of the community. This research method uses an empirical legal research method. Based on the results of the study, it shows that the implementation of drinking water provision by the Surakarta City Regional Drinking Water Company is not entirely fair and equitable to the community. This is influenced by several obstacles faced, including unstable water quality, less than optimal water continuity, damage to water pumps, and leaks in the pipe network.